SNPs in Mammary Gland Epithelial Cells Unraveling Potential Difference in Milk Production Between Jersey and Kashmiri Cattle Using RNA Sequencing - Ahmad, Syed Mudasir; Bhat, Basharat; Bhat, Shakil Ahmad; Yaseen, Mifftha; Mir, Shabir; Raza, Mustafa; Iquebal, Mir Asif; Shah, Riaz Ahmad; Ganai, Nazir Ahmad (Frontiers in Genetics, 2021)
Deep RNA sequencing experiment was employed to detect putative single nucleotide polymorphisms (SNP) in mammary epithelial cells between two diverse cattle species (Jersey and Kashmiri) to understand the variations in the coding regions that reflect differences in milk production traits.The low milk producing Kashmiri cattle is being replaced by cross breeding practices with Jersey cattle with the aim of improving milk production. However, crossbred animals are prone to infections and various other diseases resulting in unsustainable milk production. In this study, we tend to identify high impact SNPs from Jersey and Kashmiri cows (utilizing RNA-Seq data) to delineate key pathways mediating milk production traits in both breeds. A total of 607 (442 SNPs and 169 INDELs) and 684 (464 SNPs and 220 INDELs) high impact variants were found specific to Jersey and Kashmir cattle respectively. Based on our results, we conclude that in Jersey cattle genes with high impact SNPs were enriched in Nucleotide excision repair pathway, ABC transporter and metabolic pathways like Glycerolipid metabolism, Pyrimidine metabolism and amino acid synthesis (Glycine, serine and threonine). Whereas, in Kashmiri cattle the most enriched pathways include endocytosis pathway, innate immunity pathway, antigen processing pathway, insulin resistance pathway and signaling pathways like TGF beta and AMPK which could be a possible defense mechanism against mammary gland infections. A varied set of SNPs in both breeds, suggests a clear differentiation at the genomic level, further analysis of high impact SNPs are required to delineate their effect on these pathways.